2015
DOI: 10.1038/ki.2015.243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a gastrointestinal–renal kaliuretic signaling axis in humans

Abstract: A gastrointestinal-renal kaliuretic signaling axis has been proposed to regulate potassium excretion in response to acute potassium ingestion independent of the extracellular potassium concentration and aldosterone. Here we studied this presumed axis in 32 individuals in our clinical pharmacology unit while on a 20 mmol sodium and 60 mmol potassium diet. The serum potassium concentration, potassium excretion, aldosterone, and insulin were measured following either a 35 mmol oral potassium load, a potassium- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 41 publications
(85 reference statements)
7
55
0
Order By: Relevance
“…22 The existence of such feedforward mechanisms has been shown for potassium and salt. [43][44][45][46] However, Scanni et al 23 had found, in healthy humans, that the rate of elimination and overall quantity of Pi excretion did not depend on the route of application (intravenous versus intraduodenal infusion). Consistently, our data do not provide any evidence for a role of the intestine in promoting phosphaturia.…”
Section: Discussionmentioning
confidence: 99%
“…22 The existence of such feedforward mechanisms has been shown for potassium and salt. [43][44][45][46] However, Scanni et al 23 had found, in healthy humans, that the rate of elimination and overall quantity of Pi excretion did not depend on the route of application (intravenous versus intraduodenal infusion). Consistently, our data do not provide any evidence for a role of the intestine in promoting phosphaturia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the mechanisms whereby low-K + diet increases PKC activity are currently unknown. Whether hypokalemia, as-yet-unidentified gut-kidney signaling [30], or both, play causative roles are areas for future investigation. Given the evidence that WNK4 amplifies the action of PKC [31], it may also be possible that WNK4 activation by intracellular Cl − depletion is involved in KLHL3 S433-P induction.…”
Section: Discussionmentioning
confidence: 99%
“…External potassium balance includes reactive mechanisms that are either dependent (negative feedback) or independent (feed‐forward) on changes in plasma potassium . Peripheral potassium receptors with afferent connections to the central nervous system are thought to be located in the gastrointestinal tract and these mediate kaliuresis, independent of changes in plasma potassium . Contrary to previous beliefs, aldosterone and vasopressin are not involved in this process .…”
Section: Introductionmentioning
confidence: 95%